2013
DOI: 10.3758/s13414-013-0598-7
|View full text |Cite
|
Sign up to set email alerts
|

Perceivers vary in their capacity to benefit from feedback in learning to perceive length by dynamic touch

Abstract: Earlier ecologically motivated studies have revealed substantial individual differences in perceptual learning: Individuals varied in their ability to attune to a specifying variable. A possible source of these individual differences is between-subjects variation in the capacity to benefit from feedback. Although this hypothesis was postulated by Withagen & van Wermeskerken (2009), their experiment could not exclude other factors that might be involved. The aim of the present experiment was to provide a more c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
9
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 37 publications
2
9
0
Order By: Relevance
“…Although with the right hand none of the participants continued to rely on the variable, they detected in the pretest only five participants (Participants 1, 4, 5, 11, and 12) learned to detect a specifying variable with this hand. This is in line with earlier studies on length perception with the right hand that showed that participants vary in their ability to learn to detect specifying variables (Menger & Withagen, 2009 ; Rop & Withagen, 2014 ; Withagen & van Wermeskerken, 2009 ). Moreover, the present study demonstrated that participants also vary in the type of transfer.…”
Section: Resultssupporting
confidence: 92%
See 4 more Smart Citations
“…Although with the right hand none of the participants continued to rely on the variable, they detected in the pretest only five participants (Participants 1, 4, 5, 11, and 12) learned to detect a specifying variable with this hand. This is in line with earlier studies on length perception with the right hand that showed that participants vary in their ability to learn to detect specifying variables (Menger & Withagen, 2009 ; Rop & Withagen, 2014 ; Withagen & van Wermeskerken, 2009 ). Moreover, the present study demonstrated that participants also vary in the type of transfer.…”
Section: Resultssupporting
confidence: 92%
“…Because individuals have been found to vary in their perceptual learning capacities (Menger & Withagen, 2009 ; Rop & Withagen, 2014 ; Withagen & Caljouw, 2011 ; Withagen & van Wermeskerken, 2009 ), we analyzed the learning trajectories of each individual participant as well. To test whether an individual relied on a specifying variable or a nonspecifying variable, we compared for each participant in each test phase the correlation of perceived length and actual length with the correlation of perceived length and the most highly correlated nonspecifying variable, using Williams’ t-statistic (May & Hittner, 1997 ; Williams, 1959 ).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations